UV-based evaluation of ergosterol for monitoring the fungal exposure in Italian buffalo farms. Issue 22 (24th October 2017) - Vella, Filomena Monica; Laratta, Bruna
Abstract: This study provided a reliable way to identify and estimate the ergosterol in farm environments, since it is renowned that it is a specific indicator for the occurrence of molds and yeasts. The quick valuation of exposure to airborne microorganisms is essential to assess the risk to which the health of employees is subjected in working places characterized by great humidity. From this view, it is worth estimating the total biomass of molds and yeast, including viable and non-viable forms, which may cause respiratory concerns to human. Air samples were collected with a passive method and the microbial growth was evaluated with a traditional counting method. At the same time, the ergosterol was quantified from yeasts and molds. In this way, the aerosol concentrations of molds and yeasts were compared by using the two methods, the cultivation on plates, as well as through ergosterol measurement by means of UV spectroscopy. Results showed, for the first time, a positive correlation between the amount of ergosterol and the yeast cells. Based on these outcomes, the ergosterol is a statistically significant biomarker to be used to control the air quality of indoor and outdoor farm spaces, by means of a simple and direct UV procedure. Abstract : Ergosterol is used as fungal biomarker to monitor air safety.